PENGARUH KECERDASAN EMOSI, LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR DAN DAMPAKNYA TERHADAP PRESTASI BELAJAR SISWA - Halawa, Fransiscus Amonio; Fensi, Fabianus (Universitas Bunda Mulia, 2020)
This research is to analyze the effect of emotional intelligence, school environment on learning motivation and its impact on student achievement. The research methodology used is quantitative research using survey methods that are intended to provide an explanation. Survey research is research that takes a sample from a population and uses a questionnaire as a primary collection tool. There are 3 variables used, they are independent variable, mediation variable and dependent variable. Emotional intelligence and school environment as independent variables, learning motivation as mediating variables and learning achievement as dependent variables. The study involved as many as 89 students as respondents, the data were analyzed with SmartPLS 3.0. The results showed that emotional intelligence had a positive and significant effect on learning motivation, emotional intelligence had a positive and significant effect on learning achievement, the school environment had a positive and significant effect on learning motivation, the school environment had a positive and significant effect on learning achievement and learning motivation had a positive and significant effect towards learning achievement.